Nível de Informação e Comportamento Preventivo dos Usuários do Programa de Saúde da Família do Município de Patos PB frente ao Câncer Bucal - Araújo Filho, José Cadmo Wanderley Peregrino de (2009)
The aim of this research was to investigate the level of information and preventive behavior of the users assisted in the Basic Heart Units (UBS) of Family Health Care Program (PSF) of Patos-PB, regarding oral cancer. The data were collected through the application of a route of individual interview in a sample of 383 users. Of these, 267 are women (69,7%) and 116 men (30,3%), the age varied from 18 to 78 years, with 33,36 year-old average, more of the half (55,9%) with complete or incomplete fundamental teaching and 67,4% lived regularly with family income of until a minimum wage. Starting from the obtained data a descriptive statistical analysis was accomplished, being taken in consideration a numeric scale established with punctuation variation for each question of the interview route. With base in the sum of the punctuations, in agreement with each answer supplied by the user, these were classified in levels: low, medium or high of information and of preventive behavior. The results presented in relation to the level of information they were that 56,4% of the users presented low level, 36,3% medium level and 7,3% were only classified as high level, however, none of the interviewees (0%) it reached the maximum punctuation. When the level of preventive behavior was evaluated, 16,6% demonstrated low level, 49,6% medium level and 23,7% high level, in that 52 users (13,6%) they obtained the maximum punctuation. Most of the users demonstrated appropriate knowledge with relationship to the risk factors for CB, however, it was also loud the percentile of inadequate answers with relationship to the factors that are not considered of risk. More of the half (53,5%) it considers contagious CB, 278 users (72,6%) they never heard to speak in the mouth self-exam. Appropriate answers were supplied on how to proceed to detect lesion in the own mouth and that would not delay to seek for to the professional's of health (PS) aid case noticed alterations in your mouth. According to the found results we can end that the users of PSF of the municipal district of Patos-PB they present the level of information so much, as the preventive behavior related CB unsatisfactory.